“Storytelling is an ancient art”: Stories, Maps, Migrants and Flâneurs in Arnold Zable’s Selected Texts - Dagmara Drewniak (Anglica. An International Journal of English Studies)
Nadine Fresco in her research on exiled Holocaust survivors uses the term diaspora des cendres (1981) to depict the status of Jewish migrants whose lives are forever marked by their tragic experience as well as a conviction that “the[ir] place of origins has gone up in ashes” (Hirsch 243). As a result, Jewish migrants and their children have frequently resorted to storytelling treated as a means of transferring their memories, postmemories and their condition of exile from the destroyed Eastern Europe into the New World. Since “[l]iterature of Australians of Polish-Jewish descent holds a special place in Australian culture” (Kwapisz Williams 125), the aim of this paper is to look at selected texts by one of the greatest Jewish-Australian storytellers of our time: Arnold Zable and analyse them according to the paradigm of an exiled flâneur whose life concentrates on wandering the world, sitting in a Melbourne café, invoking afterimages of the lost homeland as well as positioning one’s status on a map of contemporary Jewish migrants. The analyses of Zable’s Jewels and Ashes (1991) and Cafe Scheherazade (2001) would locate Zable as a memoirist as well as his fictional characters within the Australian community of migrants who are immersed in discussing their un/belonging and up/rootedness. The analysis also comprises discussions on mapping the past within the context of the new territory and the value of storytelling.